'Up close and in person': United States and Australian political reporters' changing conceptions of the value of campaign coverage. (August 2019) - Brookes, Stephanie
The way political reporters understand their own role in election campaigns is changing, signalling a deeper shift in journalistic self-conception. In traditional discourses of journalistic identity, campaign reporters are positioned as playing a unique democratic role enabling citizens to make informed voting decisions. This article asks, 'How do campaign reporters understand and construct their own value and that of their work in an increasingly fragmented and crowded news environment?' It offers new empirical insight through a two-country study that both considers journalist perspectives and situates these within relevant theoretical debates. It analyses interviews with political reporters in the United States and Australia in 2017, guided by two conceptual frameworks that consider the ways journalists actively construct their own identity and authority: interpretive communities and metajournalistic discourse. This allows insight into the way political reporters reconsider the need to cover campaigns from 'on the bus' and defend the enduring value of being there .